2007
DOI: 10.1038/sj.ejcn.1602721
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic acid does not influence nonhaem iron absorption in humans: a comparison of kale and spinach meals

Abstract: Objective: To evaluate the influence of oxalic acid (OA) on nonhaem iron absorption in humans. Design: Two randomized crossover stable iron isotope absorption studies. Setting: Zurich, Switzerland. Subjects: Sixteen apparently healthy women (18-45 years, o60 kg body weight), recruited by poster advertizing from the staff and student populations of the ETH, University and University Hospital of Zurich, Switzerland. Thirteen subjects completed both studies. Methods: Iron absorption was measured based on erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…It is also important to note that vegetable iron sources are particularly rich in potential iron absorption inhibitors such as phytate (Kumar, Sinha, Makkar, & Becker, 2010) and some phenolic compounds like polymerized flavans (Petry, Egli, & Zeder, 2010) which can be found in legumes such as beans, faba beans are important iron sources in some populations (Luo, Xie, & Cui, 2010;Petry et al, 2010). Sotello et al (Sotelo, González-Osnaya, Sánchez-Chinchillas, & Trejo, 2010) also suggested an inhibitory role of oxalate in iron absorption from vegetable sources such as spinach or kale, however these results are not in accordance with a study which evaluated directly iron absorption from these foods (Bonsmann, Walczyk, Renggli, & Hurrell, 2008). Beans are also an important source of non-digestible carbohydrates which may impair iron absorption (Luo, Xie, & Cui, 2010.…”
Section: Meat a Valuable Iron Sourcecontrasting
confidence: 49%
“…It is also important to note that vegetable iron sources are particularly rich in potential iron absorption inhibitors such as phytate (Kumar, Sinha, Makkar, & Becker, 2010) and some phenolic compounds like polymerized flavans (Petry, Egli, & Zeder, 2010) which can be found in legumes such as beans, faba beans are important iron sources in some populations (Luo, Xie, & Cui, 2010;Petry et al, 2010). Sotello et al (Sotelo, González-Osnaya, Sánchez-Chinchillas, & Trejo, 2010) also suggested an inhibitory role of oxalate in iron absorption from vegetable sources such as spinach or kale, however these results are not in accordance with a study which evaluated directly iron absorption from these foods (Bonsmann, Walczyk, Renggli, & Hurrell, 2008). Beans are also an important source of non-digestible carbohydrates which may impair iron absorption (Luo, Xie, & Cui, 2010.…”
Section: Meat a Valuable Iron Sourcecontrasting
confidence: 49%
“…So far, only one study on proteome profiling in Fe-deficient rice roots and shoots (Chen et al, 2015) and two in maize, with one in Fe-deficient root hairs (Li et al, 2015) and the other in roots (Hopff et al, 2013), have been carried out to investigate the global protein changes or the alterations in the plasma membrane proteome, by means of two-dimensional electrophoresis (2-DE), or 1-DE coupled with matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF/MS) or LC-MS/MS. By contrast, most of the proteomic studies upon Fe deficiency have been performed in Strategy I species, including Beta vulgaris (Andaluz et al, 2006; Rellan-Alvarez et al, 2010; Gutierrez-Carbonell et al, 2016), Tomato ( Solanum lycopersicum L.) (Brumbarova et al, 2008; Genannt Bonsmann et al, 2008; Muneer and Jeong, 2015), cucumber ( Cucumis sativus ) (Donnini et al, 2010; Li and Schmidt, 2010; Vigani et al, 2017), pea ( Pisum sativum L.) (Meisrimler et al, 2011, 2016), Prunus hybrid GF 677 rootstock ( P. dulcis × P. persica ) (Rodriguez-Celma et al, 2013a), Lupinus texensis (Lattanzio et al, 2013), Hyoscyamus albus (Khandakar et al, 2013), Medicago truncatula (Rodriguez-Celma et al, 2011, 2016), citrus rootstocks (Muccilli et al, 2013), Brassica napu (Gutierrez-Carbonell et al, 2015), Populus cathayana (Zhang S. et al, 2016), and Arabidopsis (Laganowsky et al, 2009; Lan et al, 2011, 2012b; Mai et al, 2015; Pan et al, 2015; Zargar et al, 2015a,b). Most of the protein profiling studies were focused on the global protein changes in the whole roots/shoots, and few of them investigated proteome of the specific plant parts such as root hairs (Li et al, 2015), cellular compartments including root plasma membrane (Hopff et al, 2013), thylakoid membranes (Andaluz et al, 2006), and shoot microsomal fragments (Zargar et al, 2015b), as well as phloem saps (Lattanzio et al, 2013; Gutierrez-Carbonell et al, 2015).…”
Section: Proteomes Of Fe Deficiecny In Plantsmentioning
confidence: 99%
“…While some studies have found that oxalic acid (present in spinach, silverbeet and beetroot leaves) may inhibit iron absorption, recent studies suggest that its effects are relatively insignificant. 24 Calcium has also been considered an inhibitor of both haem and non-haem iron absorption, but recent research suggests that, over a long period of time, calcium has a limited effect on iron absorption (possibly due to an adaptive physiological response). 25 Nevertheless, it may be best to avoid consuming highcalcium supplements with meals.…”
Section: Iron Deficiency Anaemiamentioning
confidence: 99%